2010
DOI: 10.1007/s11269-010-9620-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of Secondary Settling Tanks Using CFD Modeling

Abstract: Amongst the principal separation processes used to treat effluents in the water industry is the sedimentation of solid particulates from the carrier fluid known as mixed liquor by the force of gravity. New York City DEP is in the process of upgrading its Upper East River water pollution control plants (WPCP's) to incorporate biological nitrogen removal (BNR). The rectangular final settling tanks (FSTs) are a central link in the treatment process and often times a limiting factor in terms of the solids handling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Furthermore, DeClercq (2003) compared his model to the Bingham and Bokil models and concluded that the Bokil model gave the best prediction of the sludge blanket height. Over the last few years, the Bokil model has also been successfully used to model the rheology of wastewater sludge (Griborio, 2004;McCorquodale et al, 2006McCorquodale et al, , 2007Ramalingam et al, 2012;Xanthos et al, 2011;Zhou et al, 2005). It is a two-parameter model that is also relatively easy to implement in a numerical framework, and it is therefore chosen for this study.…”
Section: Molecular Viscositymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, DeClercq (2003) compared his model to the Bingham and Bokil models and concluded that the Bokil model gave the best prediction of the sludge blanket height. Over the last few years, the Bokil model has also been successfully used to model the rheology of wastewater sludge (Griborio, 2004;McCorquodale et al, 2006McCorquodale et al, , 2007Ramalingam et al, 2012;Xanthos et al, 2011;Zhou et al, 2005). It is a two-parameter model that is also relatively easy to implement in a numerical framework, and it is therefore chosen for this study.…”
Section: Molecular Viscositymentioning
confidence: 99%
“…This model was later used by Ghawi and Kris (2011) to investigate the effect of inlet baffles in terms of improving the performance of the secondary clarifiers at the Al-Dewanyia WWTP in Iraq. Xanthos et al (2011) incorporated a flocculation sub-model into a 3D CFD model to improve the Upper East River water pollution control plant in New York City. More recently, Griborio, Martinez, Stanley, Koroshec, and Coates (2012) presented a comprehensive approach including field characterization and CFD modeling for the rehabilitation of three circular centerfeed secondary clarifiers at the South Central Regional Wastewater Treatment and Disposal Board located in Delray Beach, Florida.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Process release a portion of the solid from the suspension normally is carried out in settling tanks (Kowalski, 2004;Burger & Wendland, 2001;Bandrowski et al, 2001;Banaś, 2004a), that is devices using sedimentation process. The intensification of the process of sedimentation, the optimization of the process as well as the construction settlers still an important research topic (Bajcar et al, 2010(Bajcar et al, , 2011Branny & Swolkien, 2010;Rostami et al, 2011;Goula, 2008;Samaras, 2010;Xanthos, 2011;Malcher & Gzyl-Malcher, 2012;Surowiak & Brozek, 2014;Tryggavason & Zaleski, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of comprehensive studies on baffled tanks that investigate their hydraulic efficiency (McCorquodale and Zhou, 1993;Tamayol et al, 2010;Xanthos et al, 2010). Brescher et al (1992) considered a rectangular clarifier and showed that an intermediate (where intermediate refers to location along the tank length) baffle on the base of the tank, transverse to the main flow direction, influences the flow field and can improve efficiency.…”
Section: Introductionmentioning
confidence: 99%